Disease-Modifying Treatment of Psoriasis in Children - Nikolay N. Murashkin; Alexander I. Materikin; Roman V. Epishev; Mariya A. Leonova; Leonid A. Opryatin; Dmitry V. Fedorov; Roman A. Ivanov; Alena A. Savelov; Ekaterina S. Pavlov (Вопросы современной педиатрии, 2024)
Advances in understanding the mechanisms underlying chronic inflammatory skin diseases, such as psoriasis vulgaris, have led to implementation of new treatment options aimed at symptoms relieving. Moreover, this data may become the basis for new strategies to achieve sustained or treatment-free remission, that is disease modification with potential impact on comorbid conditions. However, achieving this goal requires further study of such crucial aspects as the terms of disease modification and disease activity indicators, deeper understanding of pathogenesis mechanisms, etiology, and systemic side effects, possible opportunities, biomarkers for successful patient stratification and intervention, as well as the adequate study design. Early intervention with genetically engineered biologic drugs such as secukinumab represents new paradigm shift in improvement of immune-mediated diseases outcomes. However, new evidence is needed to determine its efficacy in psoriasis. High level of sustained skin clearance observed on secukinumab therapy compared to standard treatment and phototherapy indicates the potential benefit of early biologic drugs treatment to achieve complete skin clearance and improvement in quality of life, education, and daily activities. It can also become a background for changing treatment strategies for patients with newly diagnosed moderate-to-severe plaque psoriasis. Keywords: psoriasis, children, secukinumab, disease-modifying treatment